IMPLEMENTATION OF PUSH NOTIFICATION TECHNOLOGY DURING THE GENERAL ELECTION PERIOD (PEMILU) TO SUPPORT E-GOVERNMENT - Endang Lestari Ruskan; Rahmat Izwan Heroza; Apriansyah Putra; Rudi Sanjaya (IJISCS (International Journal of Information System and Computer Science), 2021)
Since 2019, simultaneous regional head elections in Indonesia. Elections elect governors and deputy governors, regents and deputy regents, mayors and deputy mayors, members of provincial councils, and members from regency/municipal councils simultaneously. With the increase in the number of pairs of candidates selected, the information about the profiles of spouses, and the schedule of activities of the employee implementation team increases. So far, schedules obtained from banners, posters, television, radio, and others. With the development of technology, people are increasingly familiar with using the web, and gadgets information is received more quickly through social media. The purpose of this study is to apply push notification technology as a schedule reminder system for the team and the community during the election period, whether the incoming messages are read. The development method used is the waterfall: 1) analysis; 2) design; and 3) Implementation; and 4) Maintenance. The web-based notification system supports government services to employees (G2E) and government to the public (G2C) to make it easier to remember campaign schedules and other election activities, accurately and up-to-date so that they can get to know more about the profiles of candidate pairs.